2012
DOI: 10.1148/rg.322115128
|View full text |Cite
|
Sign up to set email alerts
|

Quality Initiatives: Lean Approach to Improving Performance and Efficiency in a Radiology Department

Abstract: Many hospital radiology departments are adopting "lean" methods developed in automobile manufacturing to improve operational efficiency, eliminate waste, and optimize the value of their services. The lean approach, which emphasizes process analysis, has particular relevance to radiology departments, which depend on a smooth flow of patients and uninterrupted equipment function for efficient operation. However, the application of lean methods to isolated problems is not likely to improve overall efficiency or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(105 citation statements)
references
References 15 publications
1
98
0
4
Order By: Relevance
“…8,9,[13][14][15] The success of lean business improvement methods has been previously reported at a day oncology center in the Netherlands, where authors showed 12% increase in staff member productivity after lean process improvement 5 and in a cytosuite to reduce waste associated with process variation and error. 16 On reflection, one of the greatest benefits of this project was the development of multidisciplinary teamwork after the process mapping events, which led to a new appreciation for the constraints of each craft group and how they affected patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[13][14][15] The success of lean business improvement methods has been previously reported at a day oncology center in the Netherlands, where authors showed 12% increase in staff member productivity after lean process improvement 5 and in a cytosuite to reduce waste associated with process variation and error. 16 On reflection, one of the greatest benefits of this project was the development of multidisciplinary teamwork after the process mapping events, which led to a new appreciation for the constraints of each craft group and how they affected patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced scorecards have been used in health care to provide a comprehensive picture of performance at the organizational level but have not been studied at the individual provider level. [25][26][27][28] The impact of providing physicians with comprehensive and balanced feedback on their practice patterns relative to peers in the same setting is not known. In this quality improvement initiative, our objectives were to develop a tool for comprehensive feedback to ED physicians on their practice patterns relative to peers and to evaluate the impact of such a physician feedback tool on ED resource use and associated ED quality measures, ED length of stay (efficiency measure), and return to ED (balancing measure).…”
mentioning
confidence: 99%
“…An dieser Stelle seien einige dieser Ansät-ze kurz skizziert, die je nach Bedarf angewendet und kombiniert werden kön-nen: Z. B. haben die "lean priciples", die ursprünglich aus dem Produktionssystem von Toyota stammen, Einzug in die Radiologie gefunden [24]. Dahinter verbirgt sich das Prinzip der Elimination überflüs-siger Arbeitsschritte und Vorgänge, um dadurch eine Konsolidierung des Arbeitsablaufs auf die elementaren Schritte und eine damit einhergehende Effizienzsteigerung zu bewirken.…”
Section: Ansätze Zur Effizienzsteigerung In Der Literaturunclassified